Effects of prenatal yoga exercise on hepcidin and ferritin levels in pregnant women - Tandi Bara, Farida; As’ad, Suryani; Idris, Irfan; Soraya Riu, Deviana; Ahmad, Mardiana (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Prenatal yoga is a modification of hatha yoga tailored for pregnant women. This exercise is recommended throughout pregnancy. This study aimed to determine the effect of prenatal yoga exercise on the serum levels of hepcidin and ferritin in pregnant women. The study employed a quasi-experimental design with a pre- and post-test. A total of 134 second-trimester pregnant women participated and were divided into two groups (intervention group = 62, control group = 72). The intervention group received prenatal yoga exercises for 8 weeks (twice a week), while the control group attended only the standard pregnancy class. Each group was further divided into subgroups: anemic pregnant women, normal pregnant women, and overweight pregnant women. Demographic data were obtained through a basic questionnaire, while pre-pregnancy BMI data, obstetric history, and pregnancy examinations were sourced from the KIA book. Serum hepcidin levels significantly decreased in pregnant women who participated in prenatal yoga exercises (p=0.002), with the highest significance observed in overweight pregnant women (p=0.001). The average serum ferritin levels increased in all groups but were not statistically significant (p=0.759). Regular prenatal yoga exercises can reduce serum hepcidin levels in pregnant women, with a significant reduction noted in overweight pregnant women. Ferritin levels might be influenced by iron supplementation.